2021
DOI: 10.2147/cmar.s323972
|View full text |Cite
|
Sign up to set email alerts
|

Different Clinicopathologic and Computed Tomography Imaging Characteristics of Primary and Acquired EGFR T790M Mutations in Patients with Non-Small-Cell Lung Cancer

Abstract: Purpose Although patients with primary and acquired epidermal growth factor receptor (EGFR) T790M positive non-small-cell lung cancer (NSCLC) respond to osimertinib treatment, the optimal treatment strategy differs for these two groups of patients. This study aimed to compare the clinicopathologic and computed tomography (CT) imaging characteristics between primary and acquired EGFR T790M mutations in patients with NSCLC before treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 53 publications
4
13
0
Order By: Relevance
“…Findings from a previous study by Hou et al have demonstrated that textural features can be used for the identification of primary as well as acquired T790 mutations, and the present study also reported similar results. 8 Also, the present study reported that textural features were more predictive of secondary mutations. The present study also had limitations in terms of being a singlecenter study and only utilizing T1CE and T2W MRI sequences.…”
supporting
confidence: 62%
“…Findings from a previous study by Hou et al have demonstrated that textural features can be used for the identification of primary as well as acquired T790 mutations, and the present study also reported similar results. 8 Also, the present study reported that textural features were more predictive of secondary mutations. The present study also had limitations in terms of being a singlecenter study and only utilizing T1CE and T2W MRI sequences.…”
supporting
confidence: 62%
“…These results are also partially supported by Hou et al who suggested textural features from CT images can be used to distinguish between primary and acquired EGFR T790M mutations in patients with NSCLC. 38 Limitations First, this study was retrospective and comprised a relatively small sample size. A multi-center, prospective clinical trial with a larger sample size will be required to verify our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is one of the most common malignancies and the leading cause of cancer-associated deaths worldwide ( 11 ). About 15% of Caucasian and nearly 50% of Asian advanced NSCLC patients were detected with EGFR-positive mutation, mostly in exons 18–21 ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%